MODEL OF DIGITAL SIGNATURE TECHNOLOGY BASED ON PERSONAL ATTRIBUTES - CHESHUN, VIKTOR; RYZHYI, YAROSLAV; CHESHUN, DMYTRO; CHESHUN, OLEKSANDR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Abstract. The article is devoted to the presentation of a mathematical model of the digital signature synthesis technology based on personal attributes. The paper analyzes and classifies the attributes of the signatory for use in a digital signature, defines the method of presentation and distribution of attributes in a mathematical model. In the model of technology, sets of identifying, non-identifying and contextual attributes are defined. Each value of the attribute is a binary representation of the corresponding attribute, which allows you to identify the elements of the sets as binary codes or binary vectors of attributes and use methods of working with binary numbers. To implement the technology, a scheme for generating signatures using elements of a mathematical model is proposed. The formation of a digital signature is reduced to the selection of elements of sets of identification, non-identification and contextual attributes that meet the needs or wishes of the signatory, and combining them into a single binary sequence - attribute-based digital signature (ABDS). A digital signature synthesized on the basis of binary attribute vectors, together with the plain text, can be subjected to cryptographic encryption (closing) and added to a packet with a hash signature using classic electronic digital signature technologies. It is also possible to use a digital signature ABDS attributes and in open form, without encryption, determined by the goals and needs of the signer. These two expected prospects make it possible to use the digital signature technology in electronic document management systems more widely, and the technology itself to be more flexible and more universal. The solutions are the basis of the algorithmic implementation of digital signature technology using attributes.